Non-Traditional Security Threats in Shaping Civil-Military Relations in Nepal - Karki, Binod (Unity Journal, 2024)
The concept of security has expanded beyond traditional military threats to encompass various non-traditional security challenges. The security, stability, and defense of a nation are significantly influenced by its armed forces. However, the military entities do not operate in isolation; they are an integral part of the larger society they serve. Throughout history, military institutions have not only been responsible for safeguarding a nation’s security but also played a pivotal role in shaping societal values, norms, and cohesion. The practical realm of interactions between civilians and the military encompasses both direct and indirect engagements that ordinary individuals and institutions have with the armed forces which involves discussions within legislative bodies regarding the allocation of funds, regulations, and the utilization of the military, as well as intricate negotiations between civilian and military leaders aimed at shaping and executing national security policies. Drawing on existing literature and contextual analysis with a qualitative approach, this study provides a nuanced understanding of the intricate relationship between non-traditional security dynamics and civil-military interactions in Nepal. Commencing with an exploration of the concept of non-traditional security and its applicability within Nepal, this study identifies a spectrum of non-traditional security challenges confronting the nation. Furthermore, this paper explains the intricate interplay between non-traditional security issues and the evolution of civil-military relations in Nepal.